Месть по закону: Роман / В. Ю. Денисов - Денисов В. Ю. (Вне закона, 2002)
Экземпляры: ф.13 (2003) / Инвентарный номер: 44744 / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 33 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44